2020
DOI: 10.1155/2020/1605456
|View full text |Cite
|
Sign up to set email alerts
|

Salvianolic Acid B Improves Postresuscitation Myocardial and Cerebral Outcomes in a Murine Model of Cardiac Arrest: Involvement of Nrf2 Signaling Pathway

Abstract: Survival and outcome of cardiac arrest (CA) are dismal despite improvements in cardiopulmonary resuscitation (CPR). Salvianolic acid B (Sal B), extracted from Salvia miltiorrhiza, has been investigated for its cardioprotective properties in cardiac remodeling and ischemic heart disease, but less is known about its role in CA. The aim of this study was to learn whether Sal B improves cardiac and neurologic outcomes after CA/CPR in mice. Female C57BL/6 mice were subjected to eight minutes of CA induced b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…Aberrant and prolonged ER stress contributes to multiple pathologies, since it could cause inflammation and cytotoxicity in cells and tissues. SalB attracts mounting attention as a potent antioxidant with remarkable preventive effects in multiple oxidative stress-related pathologies [25,26]. It is admitted that SalB protects from doxorubicin-related cardiac dysfunction by suppressing ER stress as well as cardiomyocyte apoptosis through TRPC3 and TRPC6 inhibition [18].…”
Section: Discussionmentioning
confidence: 99%
“…Aberrant and prolonged ER stress contributes to multiple pathologies, since it could cause inflammation and cytotoxicity in cells and tissues. SalB attracts mounting attention as a potent antioxidant with remarkable preventive effects in multiple oxidative stress-related pathologies [25,26]. It is admitted that SalB protects from doxorubicin-related cardiac dysfunction by suppressing ER stress as well as cardiomyocyte apoptosis through TRPC3 and TRPC6 inhibition [18].…”
Section: Discussionmentioning
confidence: 99%
“…These changes increased the expression of the downstream antioxidant genes heme oxygenase-1 (HO-1) and NADPH:quinone oxidoreductase 1 (NQO1), inhibited cardiomyocyte apoptosis (increased expression of the antiapoptotic gene B-cell lymphoma-2 (Bcl-2) and decreased expression of the proapoptotic gene Bcl-2-associated X (Bax) and the critical mediator of apoptosis caspase-3), preserved mitochondrial morphology and function, and improved cardiac and neurological function. The antiapoptotic and antioxidant effects of salvianolic acid B were validated in H9c2 cardiomyocytes stimulated with hypoxia/reoxygenation [ 69 ].…”
Section: Pharmacological Effectsmentioning
confidence: 99%
“…Research has demonstrated that SalB can enhance mitochondrial dysfunction, lessen reactive oxygen species (ROS) production under oxidative stress, and lessen apoptosis index, thus alleviating oxidative stress-induced intestinal cell damage [14]. A previous study on the role of SalB in cardiac arrest corroborated that administering SalB at the early stage of cardiopulmonary resuscitation could lessen myocardial injury and apoptosis, thereby preventing myocardial dysfunction and reducing end-organ damage after cardiac arrest [15]. In addition, SalB can inhibit cardiomyocyte apoptosis induced by oxygen-glucose deprivation by regulating apoptosis-related factors [16].…”
Section: Introductionmentioning
confidence: 99%